2019
DOI: 10.3390/app9040724
|View full text |Cite
|
Sign up to set email alerts
|

Novel Designated Ownership Transfer with Grouping Proof

Abstract: In the supply chain management literature, various mobile radio frequency identification (RFID) protocols have been proposed for minimizing cargo theft during transport while ensuring the integrity of the entire cargo load or transferring ownership of a tagged item to another owner. These protocols are generally called grouping proof protocols and ownership transfer protocols, respectively. However, no protocol has been proposed that can achieve both requirements. In this paper, we propose a novel designated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, when the grouping proof protocol, which safeguards comprehensive product delivery, and the tag group transfer protocol, which performs ownership transfer, are executed separately, transfer efficacy is impeded [44] [45]. Tsai et al [44] combined these two protocols for identity authentication and random number generation and proposed an ownership transfer protocol that incorporates grouping proofs, which safeguarded both the efficacy and security of tag group ownership transfer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the grouping proof protocol, which safeguards comprehensive product delivery, and the tag group transfer protocol, which performs ownership transfer, are executed separately, transfer efficacy is impeded [44] [45]. Tsai et al [44] combined these two protocols for identity authentication and random number generation and proposed an ownership transfer protocol that incorporates grouping proofs, which safeguarded both the efficacy and security of tag group ownership transfer.…”
Section: Related Workmentioning
confidence: 99%
“…During the transfer process, all the tags within a group must be simultaneously transferred, and transferring only a part of the tags is impossible. The protocol by Tsai et al [44] effectively prevents all the listed attacks. However, because it lacks a mechanism to trace manufacturers and does not record the history of ownership transfer, it is incapable of tracing the source manufacturers of products.…”
Section: Forward Secrecymentioning
confidence: 99%
“…Tsai et al [22] discussed grouping-proof protocols and ownership transfer protocols, respectively. ey found that no protocol has been proposed which can achieve both requirements.…”
Section: Some Typical Rfid Grouping-proof Protocolsmentioning
confidence: 99%
“…Tsai et al [30] proposed a new grouping proof authentication protocol that enables partial ownership transfer by guaranteeing the integrity of the tagged cargoes. The protocol was analyzed against the security attacks theoretically.…”
Section: Related Workmentioning
confidence: 99%